Selected difficulties in field studies and ways (existing and possibly) to protect against them on the example of research involving parents of adult children addicted to alcohol and representatives of treatment and social support institutions - Okólska, Katarzyna (Rodzina w systemie wsparcia i pomocy osobom z problemem alkoholowym, 2020)
The aim of the article is to show selected difficulties, which appeared on the way of carrying out research involving parents of adult children addicted to alcohol and representatives of aid institutions for families with an alcohol‑related problem. The article also presents ways to deal with them. The object of the study is constituted by difficulties which are related with the research methodology used (methodology of the grounded theory). Also as well as with the nature of the social phenomenon. It was the process of “becoming” the parent of an adult child addicted to alcohol and experience accompanying this process. Issues raised are the author’s own reflections.